Personality Traits and Stockpiling in the United Kingdom During the COVID–19 Pandemic - John Magnus Roos (European Journal of Psychology Open)
Abstract: Introduction: This study analyzes the effects of personality traits on the stockpiling of groceries in the United Kingdom during the COVID–19 pandemic. The sample is representative of the UK population in terms of age, gender, and residential area. Methods: We collected the data through five rounds of web surveys during the spring of 2020 (N = 1025). We used the Big Five Inventory (BFI–10) to measure personality traits. We analyzed the data using independent t-tests and logistic regression. Results: The independent t-tests show that “stockpilers” have a higher degree of Neuroticism and a lower degree of Agreeableness and Conscientiousness than “nonstockpilers.” Logistic regressions moreover show that differences in Neuroticism are related to other personality traits, and that differences in Agreeableness are largely related to age and residential area. The low degree of Conscientiousness among “stockpilers” remains, after we controlled for other factors in the model (i.e., personality traits, gender, age, and residential area). Discussion: We discuss the findings regarding previous research. Understanding personality traits and stockpiling is important to prepare and manage similar extraordinary situations that may occur in the future.